Psychological adaptation and health-related quality of life in inflammatory bowel disease: a 5-year follow-up study - Gabriella Martino; Emanuele M. Merlo; Carmelo M. Vicario; Federica Bellone; Clara De Francesco; Ulla Feldt-Rasmussen; Antonino Catalano; Walter Fries; Orlando Silvestro (Research in Psychotherapy: Psychopathology, Process and Outcome, 2026)
Inflammatory bowel disease (IBD), encompassing Crohn’s disease (CD) and ulcerative colitis (UC), is a chronic immune-mediated gastrointestinal condition in which long-term care increasingly involves patient-reported health, emotional functioning, and psychological adaptation. Because psychological adaptation may not parallel clinical remission, this 5-year longitudinal study examined changes in psychopathological symptoms, alexithymia, coping strategies, and health-related quality of life (HR-QoL) in 73 outpatients receiving maintenance medical treatment. We expected no uniform mean-level improvement or deterioration and hypothesised that increases in depressive and anxiety symptoms, alexithymia, and avoidance coping would be associated with poorer HR-QoL outcomes and that increases in positive attitude coping would be associated with better outcomes. Participants were reassessed during clinical remission using validated measures, and psychological changes were analysed in relation to follow-up quality of life outcomes, adjusting for baseline levels and disease duration. Mean-level changes were limited across depressive symptoms, overall anxiety, alexithymia, most coping dimensions, and HR-QoL indices. Somatic anxiety increased over time (p=.03), whereas social support coping decreased consistently in the overall sample and within both diagnostic subgroups (p